The development of an electronic geriatric assessment tool: Comprehensive health assessment for my plan (CHAMP). Issue 1 (January 2023) - Cook, Simon; Munteanu, Cosmin; Papadopoulos, Efthymios; Abrams, Howard; Stinson, Jennifer N.; Pitters, Eric; Stephens, Douglas; Lumchick, Margaret; Emmenegger, Urban; Koneru, Rama; Papadakos, Janet; Shahrokni, Armin; et al.
Abstract: Introduction: Geriatric assessment (GA) provides information on key health domains of older adults and is recommended to help inform cancer treatment decisions and cancer care. However, GA is not feasible in many health institutions due to lack of geriatric staff and/or resources. To increase accessibility to GA and improve treatment decision making for older adults with cancer (≥65 years), we developed a self-reported, electronic geriatric assessment tool: Comprehensive Assessment for My Plan (CHAMP). Materials and Methods: Older adults with cancer were invited to join user-centered design sessions to develop the layout and content of the tool. Subsequently, they participated in usability testing to test the usability of the tool (ease of use, acceptability, etc.). Design sessions were also conducted with oncology clinicians (oncologists and nurses) to develop the tool's clinician interface. GA assessment questions and GA recommendations were guided by a systematic review and Delphi expert panel. Results: A total of seventeen older adults participated in the study. Participants were mainly males (82.4%) and 75% were aged 75 years and older. Nine oncology clinicians participated in design sessions. Older adults and clinicians agreed that the tool was user-friendly. Domains in the final CHAMP tool (with questions and recommendations) included functional status, falls risk, cognitive impairment, nutrition, medication review, social supports, depression, substance use disorder, and miscellaneous items. Discussion: CHAMP was designed for use by older adults and oncologists and may enhance access to GA for older adults with cancer. The next phase of the CHAMP study will involve field validation in oncology clinics.